2011
DOI: 10.1007/s12013-011-9322-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress is Associated with Genetic Polymorphisms in One-Carbon Metabolism in Coronary Artery Disease

Abstract: In view of growing body of evidence favouring the association of aberrations in one-carbon metabolism and oxidative stress in the aetiology of coronary artery disease (CAD), we investigated the risk associated with polymorphisms regulating the folate uptake and transport such as the glutamate carboxypeptidase II (GCPII) C1561T, reduced folate carrier 1 (RFC1) G80A and cytosolic serine hydroxymethyltransferase (cSHMT) C1420T. We further evaluated the impact of seven putatively functional polymorphisms of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…In another study, we observed that GCPII 1561 C[T as a risk factor for CAD, while cSHMT 1420 C[T conferred protection [24]. GCPII 1561T and MTRR 66A-variant alleles were reported to contribute to increased oxidative stress while cSHMT 1420T and TYMS 5 0 -UTR 2R alleles reduce oxidative stress [24]. In the same cohort, we observed association of CYP1A1 m1, CYP1A1 m2 (rs1048943) and GSTT1 null with CAD risk [25].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…In another study, we observed that GCPII 1561 C[T as a risk factor for CAD, while cSHMT 1420 C[T conferred protection [24]. GCPII 1561T and MTRR 66A-variant alleles were reported to contribute to increased oxidative stress while cSHMT 1420T and TYMS 5 0 -UTR 2R alleles reduce oxidative stress [24]. In the same cohort, we observed association of CYP1A1 m1, CYP1A1 m2 (rs1048943) and GSTT1 null with CAD risk [25].…”
Section: Introductionmentioning
confidence: 70%
“…Earlier, we reported MTHFR 677 C[T, MTRR 66 A[G (rs1801394) as risk factors for CAD and TYMS 5 0 -UTR 28 bp tandem repeat polymorphism as a protective factor [23]. In another study, we observed that GCPII 1561 C[T as a risk factor for CAD, while cSHMT 1420 C[T conferred protection [24]. GCPII 1561T and MTRR 66A-variant alleles were reported to contribute to increased oxidative stress while cSHMT 1420T and TYMS 5 0 -UTR 2R alleles reduce oxidative stress [24].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our previous studies and others have shown that oxidative stress is involved in diabetes, hyperlipidemia, and smoking are the potential risk factors for CAD [40][41][42]. Oxidative DNA damage is directly or indirectly involved in the pathophysiology of CAD.…”
Section: Discussionmentioning
confidence: 93%
“…GCPII and its genetic variants are known to be associated with folate nutritional status and disease 1 susceptibility, as this is a critical locus for the absorption mechanism of methylfolate (Devlin et al, 2000). One particular mutation of this gene, C1561T in which histidine 475 is changed to tyrosine (rs61886492, H475Y), has been reported to be associated with risk for breast and prostate cancer, coronary artery disease and miscarriage (Divyya et al, 2012;Vijaya Lakshmi et al, 2013). This genetic variant may lead to a reduction in GCPII activity, and hence to a lower blood folate concentration and higher homocysteine (Hcy), potentially implicating this polymorphism in the pathoaetiology of these disorders (Devlin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%